PENGEMBANGAN MODUL PERSAMAAN GARIS LURUS UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Sofiansori Gowasa (Universitas Nias Raya, 2022)
The research method uses Research and Development (R&D) with a 4D model (Define, Design, Develop and Dessimenate). Data collection techniques used are questionnaires and tests. Data analysis techniques, namely qualitative data analysis and quantitative data analysis. Based on the results of the research and discussion, the straight line equation module meets the valid, practical and effective criteria. The validity results for validating material experts obtained an average of 86.66% very valid criteria, media expert validation obtained an average of 80% valid criteria and validation of language experts obtained an average of 92.72% very valid criteria, from the three validations obtained an average of 85.31/% criteria very valid. Practicality results in limited trials obtained an average of 4.33 with a percentage of 86.62% very practical criteria, field trials obtained an average of 4.27 with a percentage of 85.35% practical criteria and teacher response obtained 4.25 with a percentage of 86.6% very practical criteria. The effectiveness results in limited trials obtained an average of 73.15 criteria of being quite effective and field trials obtaining an average of 72.28 criteria of being quite effective. The N-Gain results show an increase in students' problem solving abilities through limited trials obtained g = 0.57 medium criteria and field trials obtained g = 0.56 moderate criteria. So it is concluded that the straight line equation module can improve students' mathematical problem solving abilities. It is expected that the developed module can be used in the process of learning mathematics on straight line equations.